Key Strategies of Visual Transmission in Social Media Marketing - Tian, Kun (Transactions on Economics, Business and Management Research, 2023)
With the popularity and rapid growth of social media, more and more enterprises begin to use social media platform for marketing and promotion. Social media platforms such as WeChat, Weibo and Tik Tok have billions of users. These users share information, exchange ideas and express emotions on the platform, which provides a huge marketing opportunities for enterprises. Visual transmission is a vital part of social media marketing, which can convey brand information through visual elements such as images, graphics, colors and typesetting, attract audience's attention and stimulate their interest. The existing research mainly focuses on brand logo design, creative design, color matching, image quality, video production and so on. This paper aims to study the key strategies of visual transmission in social media marketing, and explore the role and mechanism of visual transmission in social media marketing.